ASSESSING VOCATIONAL SCHOOL STUDENTS' WORK READINESS THROUGH INDUSTRIAL PRACTICAL EXPERIENCE AND JOB INTERESTS - Rahmah, Rafika Isnanur; Zulaihati, Sri; Sumiati, Ati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
The aim of this research is to determine the influence of industrial work practices (Prakerin) and career interests on the level of work ability of class XII students at state schools in the East Jakarta area. This research uses quantitative methods and primary data by distributing questionnaires to National Vocational School students. The sample for this research consisted of 159 respondents using a proportional random sampling technique with a Likert scale size. Data were processed using the SPSS version 29 program with several linear regression analysis techniques. The results of this research indicate that industrial work practices have a significant influence on the level of work readiness of class What is significant is that Industrial Work Practices and Career Interests together have an influence on class XII job preparation at State Vocational Schools. students from the East Jakarta area. This shows that Industrial Work Practice is a skill that students need to have to compete in the world of work and with high work interest, it will encourage students to equip themselves as much as possible with the various competencies needed for work so that their work readiness is increasingly adequate.